Anemarrhena saponins attenuate insulin resistance in rats with high-fat diet-induced obesity via the IRS-1/PI3K/AKT pathway. (15th September 2021) - Feng, Meng; Liu, Fen; Xing, Juling; Zhong, Yanhua; Zhou, Xinxin
Abstract: Ethnopharmacological relevance: Anemarrhena asphodeloides is the dry rhizome of Anemarrhena asphodeloides Bge . Anemarrhena Saponins isolated from Anemarrhena asphodeloides are one of the pharmacologically active components of this plant and have blood lipid reduction and blood glucose reduction properties. These facts suggest that these saponins might be helpful in the treatment of insulin resistance. Aim of the study: To determine the therapeutic effect of anemarrhena saponins on insulin resistance and the probable underlying mechanism. Materials and methods: Insulin-resistant rats were used as the experimental subject, to observe the therapeutic effect of anemarrhena saponins. The blood glucose and blood lipid parameters were determined using the relevant kits. We used hematoxylin and eosin (H&E) staining to observe the protective effect of anemarrhena saponins on the livers of insulin-resistant rats and reverser transcripition polymerase chain reaction (RT-PCR) to analyze the mRNA expressions patterns of genes related to glucose metabolism and inflammatory factors. The toxicity of anemarrhena saponins to HepG2 cells was calculated using the MTT assay. Further, we conducted i n vivo and in vitro experiments, and Western-blot analysis to study the effects of anemarrhena saponins on the IRS-1/PI3K/AKT pathway. Results: Anemarrhena saponins were found to improve dyslipidemia, reduce obesity and inflammation, and alleviate liver injury in insulin-resistant rats. Anemarrhena saponins also reduced the mRNA expression of gluconeogenesis-related genes sunch as G6pase, PEPCK, and GSK3β in the liver. Moreover, anemarrhena saponins up-regulated the phosphorylation levels of IRS-1, PI3K and AKT, promoted insulin signal transduction, and reduced liver injury induced by insulin resistance. Conclusions: These findings suggest that anemarrhena saponins could promote insulin signal transduction through the IRS-1/PI3K/AKT pathway, thereby reducing the damage caused by insulin resistance. Graphical abstract: Image 1 Highlights: Anemarrhena saponins could alleviate insulin resistance induced by high-fat diet. Its mechanism on insulin resistance involved activation of IRS-1/PI3K/AKT signaling pathways. Anemarrhena saponins may be a potential drugs for alleviating high-fat diet-induced insulin resistance.